Implementasi Manajemen Pemberian Makanan Tambahan Anak Sekolah (PMT-AS) sebagai Edukasi Parenting Anak Usia Dini - Utami Kumala Dewi; Nurhusna Kamil; Fadila Arnisa Harahap; Erni Munastiwi (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2024)
As the government calls for implementing the PMT-AS program, as a form of concern by paying attention to aspects of quality, and food safety. So, through parenting education, which is an informal program of PAUD institutions, it is expected to help parents have quality knowledge to be implemented in everyday life. Thus, researchers are interested in conducting research at Pangudi Luhur Jenarwetan Kindergarten, related to how the management of PMT-AS (Supplementary Feeding of School Children), especially for the 5-6 year age group, to find out what PMT-AS applications have been implemented by the institution as a form of parenting education. Researchers used qualitative research methods with a descriptive approach, while the research subjects were Pangudi Luhur Jenarwetan Kindergarten students in group B with a total of 12 students, 1 class teacher and principal, and parents. The results of this study, that the PMT-AS activity program at Pangudi Luhur Jenarwetan Kindergarten is carried out once a week, which is held on Saturday after gymnastics activities. PMT-AS menu design is made before entering the new school year, with each activity two menus (snacks and side dishes). Not only as a parenting education activity, but also as a gathering place for parents with educators and students.